Strategi Pemasaran dalam Meningkatkan Penjualan dan Pendapatan pada Usaha Ternak Entok Ditinjau dari Marketing Syariah - Naufal, Ahmad; Muawwanah, Muawwanah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This article analyses marketing strategies to increase sales and income of duck farming business in Wada’an Hamlet, Kalipepe Village, Lumajang, by reviewing the application of Islamic marketing principles. The study aims to examine marketing strategies that can enhance sales and income of Mr. Abror’s duck farming business from the perspective of Islamic marketing, to explore the implementation of Islamic values in marketing practices, and to assess the effectiveness of these strategies in building consumer trust and improving business competitiveness. The approach used is qualitative descriptive with field methods, collecting data through observation, in-depth interviews, and documentation. The results show that applying Islamic principles can increase consumer trust and loyalty, expand marketing networks, and positively impact sales and business income. However, limited market access and lack of promotional innovation remain major obstacles. Overall, the integration of Islamic marketing not only drives business economic growth but also strengthens business ethics values, though it needs to be supported by digital marketing innovations to enable the duck farming business in rural areas to develop well.